Relationship Between Anesthesia And Respiratory Recovery Non Smoking Post Operative Patient In The Recovery Room Ngudi Waluyo Wlingi - Ernawati , Naya; Ciptaningtyas , Maria Diah; Astuti, Erlina Suci; Supono, Supono (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Impaired gas exchange due to decreased lung function can inhibit the process of eliminating inhaled anesthetic substances through pulmonary exhalation. Smoking causes changes in the structure, function of the respiratory tract and lung parenchymal tissue, resulting in a decrease in lung physiology. This study aims to determine the relationship between postoperative respiratory recovery time and general anesthesia between smoking and non-smoking patients. The research design used is a comparative study with a cross sectional approach using purposive sampling techniques. Respondents totaled 30 people and were divided into 2 groups. Research analysis used the Mann-Whitney test with a=0.05. The average breathing recovery time for smokers is 2 minutes and 1 minute for non-smokers. Statistical test results showed that there was no difference in respiratory recovery time between smoking and non-smoking patients with p-value=0.550. Recommendations for future researchers to continue this research with more homogeneous respondents